Discovery study of integrative metabolic profiles of sesame seeds cultivated in different countries. (July 2020) - Lee, Bo Mi; Lee, Eun Mi; Kang, Dong Jin; Seo, Jeong-Ah; Choi, Hyung-Kyoon; Kim, Young-Suk; Lee, Do Yup
Abstract: Nutrition-compositional evaluation is critical for quality control and value determination of agricultural products. Sesame seed is an important crop worldwide, enriched with primary nutrients and bioactive compounds. Here, we metabo-typed sesame seeds cultivated in Korea (N = 20) and imported from China (N = 11), South Asia (India and Pakistan), and Africa (Nigeria and Ethiopia) based on 243 metabolites determined by the combination of GC-MS and LC-MS. First, PLS-DA coupled to VIP analysis proposed ten-metabolite recomposite for biomarker. Receiver operating characteristic (ROC) analysis demonstrated the best predictability of the ten-metabolite recomposite according to the four areas (AUCs ranged 0.93–1.00). We further interrogated the unique metabolic features of 20 Korean domestic samples. Unbiased metabo-typing of the profiles showed the strong association according to the longitudinal coordination of the cultivated regions. The resultant 3 groups presented the regional specificity in metabolite contents based on chemical enrichment analysis. Particularly, the northwest region was featured by enriched amino acids, sugar alcohols, and pyrrolidinones. The central region presented relatively higher contents in various types of sugar alcohols, indoles, and fatty acids whereas the east province and south coast showed higher contents in dicarboxylic acids and dipeptides. Highlights: The sesame profiles were acquired from 6 different countries including 20 different Korea provinces. A total of 243 primary and secondary metabolites were identified and semi-quantified. Metabolic cluster with 10 compounds discriminated the international origin. Unique metabolic features classified sesames from 20 different Korean provinces.